Diagnóstico da aplicação de cores em projetos web baseado em uma metodologia - Buchdid, Samuel Bastos (Universidade Federal de São Carlos, 2006)
This work have used a colors application methodology in the project Web, elaborated by Luciana Martha Silveira, as a systematic of analysis of virtual environments, applied here in the domain of Distance Learning (DL). That methodology presents five fundamental axes which include the physical, physiologic and symbolic aspects involved in the chromatic perception. The search for problems identification and the aiming for their possible solutions was the main goal of the present work, in agreement with the chromatic context that each site is inserted, considering the need to have a way of revising the systems Web, which are available to the visitors of those websites. The recurring problems in sites were identified in that application domain, and the solutions were aimed in regard of the methodology applied. It is waited that the formalized results in the analyses and the identification of the problem/solution pairs in that domain of colors application would be able to help the designer in chromatic composition of sites aesthetically more attractive and intuitive, including a larger degree usability.
Diagnostics of colors application in the web design based on a methodology
Keywords: Interação homem-máquina; Cores; Interfaces web; Ensino à distância; Usabilidade; Interfaces de usuários; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO